McGraw-Hill's super-mini American slang dictionary - Spears, Richard A. (McGraw-Hill, 2007)
Presents the 411 on American slang. This dictionary presents you with 2,100 entries including colorful words and phrases from television and movies, as well as the streets and campuses.